O medo à espreita : A menina morta, de Cornélio Penna - Andrade, Luiz Eduardo da Silva (2013)
Cornélio Penna (1896-1958) is known by his mysterious writing that takes effect in their novels. In A menina morta, we face a shadowy environment, marked by contrasting expressions, based in an atmosphere of fear and power. Starting from concept of chiaroscuro, the paper shows baroque traces in narrative, aiming to argue the possibility of this shadow, seemingly constant, to express methaphorically, in a reread modernist form from sixteenth century resources, the constructing of a regulated society in fear and in a veiled ban of arguments. Despite relationship caustic, though silent, the restricted subject can confront the patriarchal structure in the novel, dramatizing each more the intrigue. In this intermediate moment, the characters seem to dramatization their relationships, a reinforced trace by the anxiety of knowing they are prey into the spatial labyrinth of the house and discursive labyrinth built by some divergences that, paradoxically, moves the narrative. According to discuss some baroque traces which come up with the chiaroscuro illusion, the labyrinthic images and dramatization from some characters (MIRANDA, 1979), we belive, among other scholars, of Ávila (1971), Peyronie (1997), Sant Anna (2000) and Maravall (2002). For instance of this initial delimitation, other analysis fields are open, considering some aesthetic elements of narrative, like the labyrinth, the chiaroscuro, the oral language and the listeners/readers, are converted in social investigations tools. They are all situated on a critical interface eye which aims to elucidate fear structure functioning based by on a power maintaining that acts modeling some behaviors and discourses (FOUCAULT, 2009; 2010) in order to ensure the patriarchal system tradition.